Platelet-rich plasma as a new treatment method in orthopedics - Aleksandra Janocha; Aneta Jerzak; Anna Hitnarowicz; Bożena Kmak; Anna Szot; Agnieszka Pociecha (Journal of Education, Health and Sport, 2024)
Introduction and purpose Platelet-rich plasma (PRP) therapy represents a technology designed to enhance tissue repair by locally administering one's own bioactive agents, aiming to influence physiological processes like inflammation, angiogenesis, and extracellular matrix synthesis. Recently, the use of PRP therapy has become a subject of discussion in the orthopedic field. This review comprehensively examines the mechanisms, contemporary applications, clinical evidence, safety aspects, and potential future advancements of PRP in orthopedic treatment. Research has documented the efficacy of PRP injections in achieving full regeneration and enabling a comeback to competitive sports. PRP injections could serve as a viable alternative treatment for individuals with lateral tendonitis when compared to surgery. Further research investigating the impact of PRP on the bone healing process following a fracture is warranted.